Valuasi Desa Wisata Penglipuran: Sebuah Pendekatan Kuantitatif Menggunakan Contingent Valuation Method - Jayanegara, Ketut; Sukarsa, Komang Gde; Kencana, Eka N (Jurnal Matematika; Vol 14 No 2 (2024)DO - 10.24843/JMAT.2024.v14.i02.p178, 2024)
Penglipuran v illage is one of several tourist villages in Bali. The United Nations World Tourism Organization (UNWTO) chose this village as one of the best tourist villages in the world in 2023. Penglipuran village is famous for its unique traditional buildings and cultural attractions, as well as the cleanliness and beautiful atmosphere in the village environment. As a potential for improving the welfare of village communities, Penglipuran's attractiveness as a tourist attraction should calculated. This research aims to value its attractiveness from a tourist perspective. A hundred and sixty five domestic visitors and 130 foreign tourists were randomly selected as respondents in the survey on July - September 2023. All respondents were asked for their opinion regarding the value of the entrance ticket to Penglipuran Village that they were willing to pay. The research results show domestic tourists willing to pay IDR 3 0 , 8 00 for adult tickets and IDR 17, 280 for children's tickets. Meanwhile, foreign tourists expressed their willingness to pay an entrance ticket of IDR 38, 15 0 for adult visitors and IDR 2 1 , 38 0 for child visitors. Using th ese WTP s value and looking at the number of domestic and foreign tourists visiting o n the January - October 2023 period, the valuation of Penglipuran Tourism Village in early November 2023 around IDR 27 ,39  billion.